The McOndo movement and the poetics of Rodrigo Fresán, an overview - Domínguez Solís, Manuel (Huarte de San Juan. Filología y Didáctica de la Lengua, 2020)
The aim of this research is to study the place occupied by the literary movement McOndo in the eyes of the critic, the problems with regard to the issue of the canon and nationalism and cosmopolitism as literary topics. In order to do that the research is going to put into perspective the poetics of Rodrigo Fresán, one of the authors who was part of the socalled movement McOndo. Using the analyticmethod, this research recounts the critical problems caused by the emergence of a literary movement like McOndo. The contrast of opinions and the demonstration of the marginality of an author like Rodrigo Fresán are part of this research. In general, regarding to the literary issues shown in the poetics of Rodrigo Fresán, this research allows to study his place in the canon and the critical opinion.
Keywords: Latin American literature; McOndo; Rodrigo Fresán; national literature; cosmopolitan literature; logic irrealism